Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Kepuasan Konsumen : Survei pada Konsumen Coffee Shop Fullhoper Tasikmalaya - Dian Ahadianti; Kusuma Agdhi Rahwana; Suci Putri Lestari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of product quality and service quality on consumer satisfaction Coffee Shop Fullhoper in Tasikmalaya simultaneously and partially. By using survey research method, the sample technique used is accidental sampling and taken as many as 100 people. The analytical tools used in this research are classical assumption test andregression multiple. The results showed that the effect of product quality and service quality simultaneously had a significant effect on consumer satisfaction. Product quality and service quality partially significant effect on customer satisfaction.